Toxicidade e estresse oxidativo: efeitos de nanocápsulas com diferentes revestimentos poliméricos e nanocápsulas de colchicina em Drosophila melanogaster - (:unkn) unknown (Universidade Federal do Pampa, 2023)
In nanotechnology, polymeric coatings are used in the formulation of polymeric nanocapsules (NCs), including NCs coated with Polysorbate 80 (NCP80), polyethylene glycol (NCPEG), Chitosan (NCCS), and Eudragit (NCEUD). Polymeric coatings are chosen based on the release profile and chemical characteristics of the substance. This study aimed to compare the effects of exposure to different polymeric coatings, free colchicine (COL), and colchicine nanocapsules (NCCOL) on behavioral parameters and oxidative stress in Drosophila melanogaster. Tests assessed mortality, reactive species production, and antioxidant enzyme activity and oxidative stress biomarkers following acute and chronic exposure. Results indicate significant toxicity associated with high NC concentrations and variability in the effects of polymeric coatings on oxidative stress. Additionally, NCCOL showed reduced adverse effects compared to COL, suggesting a potentially safer therapeutic use of nanocapsules in future formulations.
Toxicity and oxidative stress: effects of nanocapsules with different polymeric coatings and colchicine nanocapsules in Drosophila melanogaster
Keywords: Drosophila; Toxicity; Toxicidade Nanoencapsulation; Nanoencapsulação; CNPQ::CIENCIAS BIOLOGICAS